The professionalism of professional youth work and the role of values - Judith Metz (Social Work and Society, 2018)
This article aims to create greater clarity about the specific professionalism of professional youth work by using the sociological theory on the phenomenon of labour division and the role that professions play in modern, western societies. Due to an unclear professional identity the existence of professional youth work within Northwest European welfare states is subject to debate. Sociological theory of professions shows that professions have three different societal roles: objective rationality, moral responsibility and democratic practice. A concise discussion of the development of professional youth work from the perspective of these three roles results in a model of professional youth work's own professionalism, with values at the core of the profession. The core values of youth work are: development-oriented, social justice and full participation. Besides, there are five preconditions that ensure the technical quality of professional practice. The preconditions are: personal commitment to young people, normative reflection, knowledge, workmanship and legitimacy, the provision of accountability of professional youth work. This article is based on literature on youth work, social work and sociological theory of professions.